The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1145/3173551
|View full text |Cite
|
Sign up to set email alerts
|

Automatically Distributing Eulerian and Hybrid Fluid Simulations in the Cloud

Abstract: Distributing a simulation across many machines can drastically speed up computations and increase detail. The computing cloud provides tremendous computing resources, but weak service guarantees force programs to manage significant system complexity: nodes, networks, and storage occasionally perform poorly or fail. We describe Nimbus, a system that automatically distributes grid-based and hybrid simulations across cloud computing nodes. The main simulation loop is sequential code and launches distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Parallel INSE solvers for multicore systems were developed using OpenMP [67] and extended to multinode cluster systems using MPI [68]. In computer graphics, Mashayekhi et al [69] proposed a system called "Nimbus", which automatically distributes grid-based and hybrid simulations across cloud computing nodes for faster execution at higher grid or particle resolutions.…”
Section: Parallel Navier-stokes Solversmentioning
confidence: 99%
“…Parallel INSE solvers for multicore systems were developed using OpenMP [67] and extended to multinode cluster systems using MPI [68]. In computer graphics, Mashayekhi et al [69] proposed a system called "Nimbus", which automatically distributes grid-based and hybrid simulations across cloud computing nodes for faster execution at higher grid or particle resolutions.…”
Section: Parallel Navier-stokes Solversmentioning
confidence: 99%
“…Although there has been research utilising multiple servers to distribute the task of solving physics based problems (e.g., [Mashayekhi et al 2018]), to the best of our knowledge there is no literature describing real-time interactive physics exploiting the addition of servers to gain scalability. The closest work to our research is that carried out to seek scalability in terms of player numbers in online gaming in the field of Distributed Virtual Environments (DVEs).…”
Section: Background and Related Workmentioning
confidence: 99%
“…Running a simulation 10 times faster on 10 times more nodes costs the same but completes an order of magnitude faster. Recent work has shown that single‐threaded complex simulations can be automatically distributed to run on over a thousand cores in the cloud, drastically speeding up simulations and increasing their details [MSQ*18].…”
Section: Introductionmentioning
confidence: 99%